Perancangan User Interface Aplikasi Aritmatika Tingkat Rendah Menggunakan Metode Design Thinking - Miladia Nurunnisa; Nadila Puspita Nuryadi; Sinta Solihat (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2022)
Arithmetic is a material in mathematics, which includes learning basic operations such as addition, subtraction, multiplication, and division. Mathematics is a subject that has various levels of difficulty from low to high. The way of delivery in learning also affects student learning outcomes, if the teacher can convey mathematical material well, students will find it easy to work on problems or digest the material provided. To increase students' interest in arithmetic, a learning media is designed that can support learning, and increase student interest in low-level arithmetic learning. The learning media designed are in the form of "I Can Math" games. In designing this application using the design thinking method. Design thinking is a method used to solve practical and creative problems where the user is the main focus. In this design thinking method, decisions are made based on the needs of the user. The data collection method carried out in this study used qualitative data collection methods. By designing this application, it is possible for children to find this arithmetic material fun because it is supported by an attractive interface design. This can indicate that this application can be used as a learning media facility at the SD/MI level.